Our Burmese Days: a personal odyssey in the context of the British Colonial past - Silva, Elisabete Mendes (2015)
Our Burmese Days embodies a revealing documentary about the past of a Eurasian family and it is a glimpse of life in a country haunted by an imperial past. The director Lindsey Merrison takes her mother back to Burma, the place where she was born, even though this was a secret kept from her and her brother until they were adults. The mother, Sally, an immigrant to England in the late 50s, ashamed of her heritage insists in denying her Burmese identity by cultivating an impeccable, flawless English accent, and by claiming that she feels English and that she was born in England. Given that the documentary’s title comes from George Orwell’s novel Burmese Days, it is thus relevant to draw some comparison between Sally’s prejudice towards Burma, a former British colony, and its culture, and one of Burmese Days’ key character, U Pu Kin, who strives to be on the side of the British and to become a parasite upon them. The main purpose of this paper is to comment on some scenes of the documentary, sketching some passages of Orwell’s novel that might have some resemblance with the documentary.